A daily-diary study on the effects of face-to-face communication, texting, and their interplay on understanding and relationship satisfaction - Monique M.H. Pollmann (Elsevier, 2021)
There is conflicting literature regarding the associations between CMC communication (especially texting) and relationship outcomes in established romantic relationships. These discrepancies could be in part because of differences and imperfections in the methodology of earlier studies, which often study CMC in isolation from other forms of communication. To address this gap in the literature, we used a daily-diary study, in which we asked people to report on the time they spent in phone calls, video calls, and texting with their partner, as well as the time they spent face-to-face with their partners. Each day we also asked participants the extent to which they felt understood by their partner and satisfied with their relationships. Results of our multilevel analyses indicated that the more face-to-face communication participants had with their partners, the more understood they felt and the more satisfied they were with their relationship. Texting, by contrast, did not predict relationship satisfaction. Texting was positively associated with understanding, but only when face-to-face communication was relatively low. These findings differ from those found in cross-sectional studies and suggest that texting should be investigated in concert with other forms of communication, especially face-to-face communication.